Remaining on the being itself: the power of bodies and affects in Spinoza (Fractal: Journal of Psychology, 2009)
This article aims mainly to cover some passages of the Ethics of Spinoza, searching to delimit the place and the importance of the notion of body in his thought. During this course, other fundamental questions correlated to the central subject are also approached, such as the concepts of substance and power, as well as the relations between body and mind. Finally, it looks to delimit the specific place of the human body, articulating it with the decisive place for the affection in Espinoza's theory. With this course the article searches also to accentuate the basic importance of the notions of life and immanence in its theory.